2011
DOI: 10.1016/j.jnucmat.2011.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundary engineering of austenitic steel PNC316 for use in nuclear reactors

Abstract: Austenitic stainless steel PNC316 was subjected to grain boundary engineering (GBE). It was found that the grain boundary engineered PNC316 (PNC316-GBEM) had a coincidence site lattice (CSL) fraction of 86% and that the network of random grain boundaries was perfectly divided by the CSL boundaries. The thermal stability and the void swelling behavior of PNC316-GBEM were investigated by means of SEM and TEM analyses. After thermal aging at 973 K for 100 h, structural changes were observed neither in the grain b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 23 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…These results present an interesting opportunity for designing radiation-tolerant materials, i.e., the grain boundary character of polycrystalline materials can be engineered to enhance their beneficial effects while reducing their detrimental effects, as was first proposed by Watanabe 16 . Recent advances in both experimentally measuring the grain boundary character distribution [17][18][19][20][21] and applying grain boundary engineering to various material systems 22 may allow for improved materials design of radiation-tolerant materials through thermo-mechanical processing. However, while experiments can readily supply information pertaining to changes in macroscopic properties due to grain boundary engineering, it is difficult to experimentally understand the behavior of grain boundary character for individual boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…These results present an interesting opportunity for designing radiation-tolerant materials, i.e., the grain boundary character of polycrystalline materials can be engineered to enhance their beneficial effects while reducing their detrimental effects, as was first proposed by Watanabe 16 . Recent advances in both experimentally measuring the grain boundary character distribution [17][18][19][20][21] and applying grain boundary engineering to various material systems 22 may allow for improved materials design of radiation-tolerant materials through thermo-mechanical processing. However, while experiments can readily supply information pertaining to changes in macroscopic properties due to grain boundary engineering, it is difficult to experimentally understand the behavior of grain boundary character for individual boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…For polycrystalline materials, the grain boundary characteristics are notably significant and exceedingly affect both the mechanical and physical properties of a material [ 1 , 2 ]. For example, the diffusion/sliding/precipitation behaviors of grain boundary significantly depend on the grain boundary features [ 3 ]. Grain boundary engineering (GBE) is an effective method to optimize the grain boundary features for improving material properties [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of GBE is to enhance the grain-boundary-related properties of materials by increasing the frequency of low Σ CSL grain boundaries (Σ≤29) and tailoring the grain boundary network. It was reported that in some face centered cubic materials with low stacking fault energy, such as Ni-based alloys [5][6][7][8] , lead alloys [9,10] , austenitic stainless steels [11][12][13][14] and copper alloys [15,16] , the frequency of low Σ CSL grain boundaries can be greatly increased by using proper thermo-mechanical processing (TMP), and as a result the grain boundary related properties were greatly enhanced. GBE is usually applied though thermo-mechanical processing which includes different combinations of strain and annealing.…”
Section: Introductionmentioning
confidence: 99%